Time trend of infant mortality in Pernambuco, 2001-2019: a population-based ecological study - Lígia Maria de Sousa Coelho; Ana Carolina Furtado Ferreira; Rebeca de Araújo Vasconcelos; Thaís Silva Matos; Carlos Dornels Freire de Souza (Instituto Materno Infantil de Pernambuco, 2023)
Abstract Objectives: to analyze the temporal trend and spatial distribution of infant mortality in Pernambuco from 2001 to 2019. Methods: an ecological study involving all deaths in children under one year of age living in the state. Data were collected from the Mortality Information System and the Live Birth Information System. Four mortality rates were calculated and the temporal analysis was performed by applying the regression model by inflection points of the rates at different spatial levels. Results: 47,949 deaths were recorded, of which 51.0% (n=24,447) occurred in the first six days of life. A statistically significant downward trend was observed in all the rates analyzed (-4.5%/year in overall mortality, -3.6%/year in early neonatal mortality, -1.9%/year in the late neonatal component, and -6.3%/year in the post-neonatal component). Additionally, 64.3% of the municipalities (n=119) showed a declining trend in the overall infant mortality rate. Less than 50% of the municipalities showed a downward trend in early neonatal and late neonatal mortality (41.08%; n=76 and 43.2%; n=80, respectively). In post-neonatal mortality, 57.3% (n=106) showed decreasing trends. Conclusions: there was a temporal trend of decline in overall infant mortality, although there is an important portion of municipalities with a stationary trend, justifying the need to reduce social inequalities and geographical asymmetries.